Optimalisasi Media Digital Dalam Pembelajaran Ekonomi - Muh. Syata, Wahyu; Mardhatillah Sabillah, Bellona; Damayanti; Subur, Hikmayani; Juwantho Lewa, Muhammad (Universitas Islam Ahmad dahlan, 2024)
Learning media are all types of physical equipment that aim to convey information and create interaction. Media used in learning, such as print and text media, audio media, moving images, multimedia media, and web-based or internet media. This research uses literature review research. In learning economics, optimizing digital media can help students improve their critical and creative thinking skills and increase their ability to learn. Various learning settings can be done using digital media, moving from individual to collaborative between students and students and students and teachers. Digital media in learning is very helpful for teachers and students in the learning process, it makes learning younger, makes the material easier to understand, makes the learning process more efficient, and achieves learning objectives. Teachers also act as facilitators, motivators and role models for their students, encouraging them to work harder in the classroom and utilize the ever-evolving technological media to access information sources relevant to economic learning objectives. By applying digital media in learning economics, students are able to broaden their understanding of economics that covers a wide range of contexts both theory and practice and know the relationship between events that occur in economics